Osnove zemljišnoknjižnog prava - Čizmić, Jozo; Šago, Dinka; Kačer, Blanka (2018)
Fundamental Principles of Land Registration Law. The book is a coursebook for students of integrated undergraduate and graduate University studies of Law, Specialist Graduate University study of Administrative Law (Faculty of Law, Split) and a Graduate University study of Geodesy (Faculty of Civil Engineering, Architecture and Geodesy, University of Split). The book is divided into eight chapters. Chapter one introduces the fundamental concepts and gives an overview of court proceedings course. Chapter two deals with activities of geodesists and judicial proceedings involving geodesists. Chapter three presents fundamental concepts and principles of Land registration law. Chapter four, deals with Land registration organizational procedural law, and also with land registers’ structure, entry types, legal effects of entries in land register. Chapter five explains objects of entries in the land register. Chapter six deals with functional procedural law, and chapter seven with specific types of proceedings. Final chapter summarizes the contents of the book in a concise explanation of the relationship between cadastre and land register.
Keywords: geodesists; cadastre; objects of entry; court proceedings; land registration law